1970
DOI: 10.1070/pu1970v013n03abeh004263
|View full text |Cite
|
Sign up to set email alerts
|

Critical Currents in Superconductors

Abstract: The ratio of circular to linear polarization cross sections for multiphoton ionization of hydrogen by intense electromagnetic fields is obtained. A cross over in dominance is seen to occur at large photon number; but this is offset by the cross section then being many order of magnitude smaller than that for the dominant process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
51
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(57 citation statements)
references
References 0 publications
6
51
0
Order By: Relevance
“…In the case of haloacetates, they were estimated by linear interpolation. A typical correlation between AH'f, 29s MAn(c) and the Edwards parameter of the correponding acids [8] are shown in Fig. 1.…”
Section: Ah'r 29s Man(c) = Ah~ 298 Man(c) -Ah~ ~+ (S) -N Ai-]~ 29sa(g)mentioning
confidence: 98%
See 2 more Smart Citations
“…In the case of haloacetates, they were estimated by linear interpolation. A typical correlation between AH'f, 29s MAn(c) and the Edwards parameter of the correponding acids [8] are shown in Fig. 1.…”
Section: Ah'r 29s Man(c) = Ah~ 298 Man(c) -Ah~ ~+ (S) -N Ai-]~ 29sa(g)mentioning
confidence: 98%
“…Later it was demonstrated that this parametr is related to the log pI~ of the corresponding acid as H = pK, + 1,74; however, as indicated in the review [8], it is more universal than pK~, being determined for strong acids.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…It should be noted that in chemical handbooks the same values of the dissociation constants for benzenesulphonic and p-toluenesulphonic acids in aqueous solutions (2 x 10 -1 at 25~ are given. According to [4] in most cases the dissociation constants of acids correlate with the Edwards parameters reflecting variations of electron-donor power of anions.…”
Section: Introductionmentioning
confidence: 97%
“…Previously [1,2] for uranyl haloacetates as an example it has been shown that extremely small variations in the anion electron-donor power [3,4] give rise to significant variations in the characteristics of salts and their behaviour in extraction. In particular, the distribution coefficients of uranium and a series of rare-earth elements [5] in trichloroacetate media increase several tens or several hundred times in comparison with the corresponding nitrate media in extraction with ethers, ketones, and trim-butyl phosphate.…”
Section: Introductionmentioning
confidence: 99%